“La globalización y sus efectos en las pymes, caso Industria Textil AUBEA BS, provincia Tungurahua, ciudad Ambato, año 2025”. - Lalangui Chicaiza, Ericka Dayanna (2025)
Globalization has profoundly transformed market dynamics at the international, national, regional, and local levels, generating both opportunities and challenges for small and medium-sized businesses. The research aimed to analyze the effects of globalization on PYMES, using the AUBEA BS textile industry, located in the city of Ambato, Tungurahua province, year 2025. Fur it, a multimodal methodology with a qualitative approach was applied, using techniques such as observation of the microenterprise, structured interviews with the owner and three experts from the Pelileo textile industry, and a Likert-type survey to the nine workers. Cronbach's alpha coefficient was applied with the support of SPSS software, resulting in a high reliability value of 0.80. The study included a comparative analysis that contrasted the results with previous research, which showed that AUBEA BS has strengths in sustainability and organizational culture; however, it faces limitations in technological access, financing, and government support, which impact its competitiveness in a globalized environment. In determining the impact of globalization on PYMES, actions were proposed to address multidimensional challenges (economic, political, legal, social, cultural, technological, and environmental). In conclusion, the findings show the need to strengthen the organizational structure, invest in innovation, progressively automate processes, and consolidate institutional alliances. Finally, the proposal is to implement a comprehensive plan focused on training, automation, access to financing, and active participation in local and international fairs to successfully address the phenomenon of globalization.